PERAMALAN PENJUALAN BATU GAMPING PADA UD EKO JAYA MENGGUNAKAN SINGLE EXPONENTIAL SMOOTHING DAN DOUBLE EXPONENTIAL SMOOTHING - Achmad David Mico; Deni Arifianto; Amalina Maryam Zakiyyah (Program Studi Akuntansi, 2022)
UD Eko Joyo is one of the limestone producers located in Grenden village. UD Eko Joyo does not yet have an application system to predict limestone sales where data collection is done manually by writing item data in the sales book. The purpose of this study is to facilitate the demand for limestone in order to reduce the difference in the average number of demand stocks. This study resulted in a Limestone Sales Forecasting System at UD Eko Joyo using Single Exponential Smoothing and Double Exponential Smoothing in the output of a website-based application with constants for single Single Exponential Smoothing testing 9 times with an alpha value of 0.1 1 to alpha 0.9. Testing for Double Exponential Smoothing is 81 times with alpha 0.1 to alpha 0.9 where at each alpha the second smoothing is also calculated with the sought beta value of beta 0.1 to beta 0.9.